2012
DOI: 10.1016/j.jviromet.2012.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Xpert Flu rapid nucleic acid testing with rapid antigen testing for the diagnosis of influenza A and B

Abstract: Influenza infections are associated with thousands of hospital admissions and deaths each year. Rapid detection of influenza is important for prompt initiation of antiviral therapy and appropriate patient triage. In this study the Cepheid Xpert Flu assay was compared with two rapid antigen tests, BinaxNOW Influenza A & B and BD Directigen EZ Flu A + B, as well as direct fluorescent antibody testing for the rapid detection of influenza A and B. Using real-time, hydrolysis probe-based, reverse transcriptase PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 20 publications
2
20
0
1
Order By: Relevance
“…This is the first time that the Xpert Flu rapid diagnostic test has been evaluated in a high-acuity ED population, where undifferentiated patients are evaluated and treated. In this high-acuity target population, Xpert Flu had high overall sensitivity and specificity compared those of ProFluϩ, similar to what has been reported by several previous studies performed in more general patient populations (4,(8)(9)(10)(11)(12)(13). From a clinical viewpoint, diagnosing influenza and initiating antiviral treatment in the admitted population is most critical, as antivirals have shown substantial benefit, including a reduction in mortality rates, in this population (14-16).…”
supporting
confidence: 84%
“…This is the first time that the Xpert Flu rapid diagnostic test has been evaluated in a high-acuity ED population, where undifferentiated patients are evaluated and treated. In this high-acuity target population, Xpert Flu had high overall sensitivity and specificity compared those of ProFluϩ, similar to what has been reported by several previous studies performed in more general patient populations (4,(8)(9)(10)(11)(12)(13). From a clinical viewpoint, diagnosing influenza and initiating antiviral treatment in the admitted population is most critical, as antivirals have shown substantial benefit, including a reduction in mortality rates, in this population (14-16).…”
supporting
confidence: 84%
“…In another retrospective study with frozen nasopharyngeal specimens from adult and pediatric patients, the authors reported sensitivities of 62.2% and 54.5% by BinaxNOW for influenza A and influenza B, respectively, compared with real-time RT-PCR (15). In our study, we found better sensitivities for BinaxNOW for detection of influenza A (72.8%) and influenza B (70.8%) than for real-time RT-PCR.…”
Section: Discussionsupporting
confidence: 45%
“…In our previous study (1), the Xpert Flu test exhibited respective sensitivity (Se) and specificity (Sp) values of 100% and 100% for the detection of influenza A virus (Flu A), 98.4% and 100% for the detection of H1N1-2009, and 80.77% and 100% for the detection of Flu B. A low sensitivity (76.5%) for Flu B detection was also reported by Li et al (2), whereas other studies reported sensitivity and specificity values ranging from 87.5% to 100% and from 99.2% to 100%, respectively (3)(4)(5)(6) (1), we compared the results observed with the Xpert Flu assay with those of the real-time RT-PCR assay routinely used (Table 1) (7). As recommended by the manufacturer, 300 l of the 1-ml swab's medium was loaded into an Xpert cartridge and processed on a 4-module GeneXpert system.…”
mentioning
confidence: 77%